Els orígens de la paremiologia catalana contemporània - Conca, Maria; Guia, Josep (Caplletra. Revista Internacional de Filologia, 2014)
In this contribution the author deals with the compilations of proverbs in the XVIII century and within the Catalan sphere of influence. These were the products of lexicographic interest produced by the Illustration throughout Europe.